Career Development Challenges In Strengthening The Performance Of The Polri Baintelkam - Bagus Herwasto Nurwicaksono, Michael; Chryshnanda Dwilaksana; Payaman Jan Simajuntak (UNES Law Review, 2023)
This research aims to address the issue of retention among members of Baintelkam Polri by identifying the problems and factors hindering career development within the organization. Despite the implementation of career coaching, retention issues persist. The research seeks to formulate a more effective strategy for career development within the Indonesian National Police Security Agency. The theoretical frameworks utilized include career management theory, performance theory, career coaching concept, and strategy concept, as well as relevant police regulations. The research adopts a qualitative approach, employing field research. The results of this research show that there are a number of problems and challenges that must be faced in career development for the National Police Security Agency. The main challenge in the internal aspect is maintaining the security and confidentiality of intelligence information amidst dynamic changes in the global environment, with threats such as the latest technology, cyber threats, and high levels of stress due to sensitive tasks. The next challenge comes from external aspects originating from cooperation problems, including with other institutions, as well as technical and information security issues. Strategies in a better career development system to strengthen the performance of the National Police's Security and Intelligence Agency have so far been implemented through career planning, job rotation and the use of technology.